Application of Finite Element Method in High Frequency Simulations - Friedl, G. (Acta Technica Jaurinensis, 2014)
This paper is written in the frame of the usage of finite element method at high frequencies. Simulations in time and frequency domain have their own methodology, for example the setting of the excitations and boundary conditions. The paper presents the weak forms of both domains derived from Maxwell’s equations and from the Sommerfeld radiation condition, simulations in isotropic and linear media, and if it is possible, comparisons between the simulations and analytical results. The first part of the paper is about the theory of the electromagnetics, the form of the wave equations in time and frequrncy domain, and about the nodal finite element method. The second chapter is about deriving the weak forms, and about their implementation method. The final chapter shows the implementation of the finite element method, and some results in time and frequency domain with differelt geometry and boundary conditions.